Γδ T-cell subsets in HIV controllers: potential role of Tγδ17 cells in the regulation of chronic immune activation. (1st July 2019) - Chevalier, Mathieu F.; Bhatnagar, Nupur; Didier, Céline; Lopez-Gonzalez, Moises; Pavie, Juliette; Bollens, Diane; Duvivier, Claudine; Collias, Lio; Jung, Corinne; Scott-Algara, Daniel; Girard, Pierre-Marie; Weiss, Laurence
Abstract : Objectives: HIV controllers (HICs) are rare HIV-infected individuals able to maintain undetectable viremia in the absence of antiretroviral treatment. Although HIV-specific cytotoxic T cells have been well deciphered in HIC, γδ T lymphocytes remain largely uncharacterized. The aim of this study was to analyse phenotypic and functional characteristics of γδ T cells and their relationship with immune activation, which remains abnormally elevated and associated with comorbidities in HICs. Methods: Peripheral blood mononuclear cells (PBMCs) were isolated from 16 HICs, 16 patients with untreated chronic HIV infection (UT-CHI) and 20 healthy donors. Surface marker expression and cytokine production by γδ T cells were analysed by flow cytometry. Results: Despite normal frequencies of total γδ T cells, the Vδ2 + /Vδ2 neg ratio was significantly reduced in HIC, albeit to a lesser extent than UT-CHI patients. Of note, nine HICs showed elevated Vδ2 neg γδ T cells, as patients with UT-CHI, which was associated with higher CD8 + T-cell activation. Interleukin (IL)-17-production by γδ T cells (Tγδ17) was better preserved in HIC than in UT-CHI patients. Proportion of total γδ T cells positively correlated with CD8 + T-cell activation and HIV-DNA, IP-10 and sCD14 levels. Conversely, Tγδ17 cells negatively correlated with CD8 + T-cell activation and plasma sCD14 levels. Moreover, transforming growth factor (TGF)-β producing Vδ2 + T cells were as dramatically depleted in HIC as in UT-CHI patients. Conclusion: The relative preservation of IL-17-producing γδ T cells in HIC and their negative association with immune activation raise the hypothesis that Tγδ17 cells – potentially through prevention of microbial translocation – may participate in the control of chronic systemic immune activation. Abstract : Supplemental Digital Content is available in the text